Analisis Buyback Saham Tanpa Rapat Umum Pemegang Saham di PT. Aneka Tambang (Studi Pada Surat Edaran Nomor 3/SEOJK.04/2020) - M. Boy Singgih Gitayuda (Universitas Islam Balitar, 2021)
In early 2020, stock trading in Indonesia was under significant pressure, as indicated by the decline in the IHSG. This is due to the pressure and global economic slowdown due to the Covid-19 pandemic and weakening world oil prices. The purpose of this study was to find out how the effect of share buyback announcements without the RUPS on the response to the market at PT. Aneka Tambang Tbk. based on Surat Edaran OJK Nomor 3/SEOJK.04/2020. This research is structured with a quantitative method with a descriptive approach using secondary data types obtained from finance.yahoo.com and other relevant sources. This study will assess whether a significant difference is found before the announcement of the stock buyback and afterwards on the return, abnormal return, and trading volume activity of the stock. The results of the study stated that there was no significant difference before and after the announcement of the stock buyback on the return and abnormal return at PT. Aneka Tambang Tbk. However, a significant difference was found in the trading volume activity (TVA) before the announcement of the share buyback at PT. Aneka Tambang Tbk. and after.